Symposium on Artificial Intelligence for Development (AI-D) - Horvitz, Eric (2010)
This collection contains a set of articles and position papers on Artificial Intelligence for Development (AI-D). Each paper explores one or more opportunities for harnessing AI to promote the socioeconomic development and to enhance the quality of life of disadvantaged populations, including those within developing countries.